Use of remdesivir in children with COVID-19 infection: a quick narrative review - La Tessa, Andrea; Motisi, Marco Antonio; Marseglia, Gian Luigi; Cardinale, Fabio; Licari, Amelia; Manti, Sara; Tosca, Mariangela; Del Giudice, Michele Miraglia; De Filippo, Maria; Galli, Luisa; Chiappini, Elena (Acta Biomedica Atenei Parmensis, 2021)
SARS-CoV-2 infection has a severe course in a small percentage of children. Remdesivir has shown promising results in reducing hospitalisation time in adults, but data on mortality rate are conflicting and few studies are available on its use use in antivirals in children. We performed a quick narrative review of the available literature data regarding the usage of remdesivir in children and neonates. In children, remdesivir showed good safety profile, however bradicardia events have been reported in children. Remdesivir is currently recommended by several guidelines in some subgroups of children with severe COVID-19, and should also be considered in critically ill patients, always in the context of the overall clinical picture and drug availability.